The Effect of Nigella sativa Extract on the Growth of Pseudomonas aeruginosa Isolated from Patients with Chronic Suppurative Otitis Media - Zihazia Leumita; Harry Agoestaf Asroel; Devira Zahara; Ziza Putri Aisyia Fauzi (LPPM Universitas Abdurrab, 2025)
Chronic Suppurative Otitis Media (CSOM) is a persistent middle ear infection often associated with Pseudomonas aeruginosa, a multidrug-resistant bacterium. Nigella sativa, commonly known as black seed, is known to have antimicrobial properties and is traditionally used in alternative medicine. This study aims to evaluate the inhibitory effect of Nigella sativa extract on the growth of Pseudomonas aeruginosa isolated from ear secretions of CSOM patients. A laboratory experimental study was conducted using ear discharge specimens from patients diagnosed with CSOM. The bacteria were cultured and identified as P. aeruginosa. Ethanol extract of Nigella sativa was prepared in various concentrations (25%, 50%, 75%, and 100%). The antibacterial activity was measured using the disc diffusion method by assessing the inhibition zone diameters. The Nigella sativa extract demonstrated a concentration-dependent antibacterial effect. The largest inhibition zone was observed at 100% concentration, with a mean diameter of 16.1 mm, indicating vigorous antibacterial activity against P. aeruginosa. Statistical analysis showed significant differences in inhibition zone diameters across concentrations (p < 0.05). Nigella sativa extract exhibits promising antibacterial activity against Pseudomonas aeruginosa isolated from CSOM patients. It has potential as a natural therapeutic alternative for treating infections associated with CSOM.